The New MIRUS System for Short-Term Sedation in Postsurgical ICU Patients*. Issue 9 (September 2017) - Romagnoli, Stefano; Chelazzi, Cosimo; Villa, Gianluca; Zagli, Giovanni; Benvenuti, Francesco; Mancinelli, Paola; Arcangeli, Giulio; Dugheri, Stefano; Bonari, Alessandro; Tofani, Lorenzo; Belardinelli, Andrea; De Gaudio, A. Raffaele
Abstract : Objectives: To evaluate the feasibility and safety of the MIRUS system (Pall International, Sarl, Fribourg, Switzerland) for sedation with sevoflurane for postsurgical ICU patients and to evaluate atmospheric pollution during sedation. Design: Prospective interventional study. Setting: Surgical ICU. February 2016 to December 2016. Patients: Postsurgical patients requiring ICU admission, mechanical ventilation, and sedation. Interventions: Sevoflurane was administered with the MIRUS system targeted to a Richmond Agitation Sedation Scale from –3 to –5 by adaptation of minimum alveolar concentration. Measurements and Main Results: Data collected included Richmond Agitation Sedation Scale, minimum alveolar concentration, inspired and expired sevoflurane fraction, wake-up times, duration of sedation, sevoflurane consumption, respiratory and hemodynamic data, Simplified Acute Physiology Score II, Sepsis-related Organ Failure Assessment, and laboratory data and biomarkers of organ injury. Atmospheric pollution was monitored at different sites: before sevoflurane delivery (baseline) and during sedation with the probe 15 cm up to the MIRUS system (S1) and 15 cm from the filter-Reflector group (S2). Sixty-two patients were enrolled in the study. No technical failure occurred. Median Richmond Agitation Sedation Scale was –4.5 (interquartile range, –5 to –3.6) with sevoflurane delivered at a median minimum alveolar concentration of 0.45% (interquartile range, 0.4–0.53) yielding a mean inspiratory and expiratory concentrations of 0.79% (SD, 0.24) and 0.76% (SD, 0.18), respectively. Median awakening time was 4 minutes (2.2–5 min). Median duration of sevoflurane administration was 3.33 hours (2.33–5.75 hr), range 1–19 hours with a mean consumption of 7.89 mL/hr (SD, 2.99). Hemodynamics remained stable over the study period, and no laboratory data indicated liver or kidney injury or dysfunction. Median sevoflurane room air concentration was 0.10 parts per million (interquartile range, 0.07–0.15), 0.17 parts per million (interquartile range, 0.14–0.27), and 0.15 parts per million (interquartile range, 0.07–0.19) at baseline, S1, and S2, respectively. Conclusions: The MIRUS system is a promising and safe alternative for short-term sedation with sevoflurane of ICU patients. Atmospheric pollution is largely below the recommended thresholds (< 5 parts per million). Studies extended to more heterogeneous population of patients undergoing longer duration of sedation are needed to confirm these observations.